Consumer behavior - Ruvio, Ayalla (John Wiley & Sons, Inc., 2024)
The intention of this textbook is to provide a contemporary, fresh voice for Consumer Behavior for undergraduates, MBAs, and Executives. Consumer behavior is a course that students usually like, in part because they can relate to it - we are all consumers, after all. Our book is positioned to help professors edutain their students. We want this book to be the one that students actually choose to read